Metaphors of the teacher role in an intervention on bullying at school - Sonia Pía Podestá González (Escuela de Psicología, Pontificia Universidad Católica de Valparaíso, 2019)
Bullying has been studied from various viewpoints: individual, interactions, and general context-centered perspectives. Current views address the context in which this problematic issue arises, with a focus on socialization processes and, therefore, on the various social actors involved. These new perspectives bring forth changes in the ways of understanding the teaching role and its functions within school intervention. The purpose of this paper is to present an analysis of the teaching role and their participation in educational intervention projects that made part of the «Stop Bullying» awareness campaign that took place in Sant Boi de Llobregat, Barcelona, Spain, during 2017. A qualitative metaphoric analysis of information gathered through participant observation is presented. The author proposes five metaphors for various teachers' roles in these intervention projects, such as methodological resources which allow comprehending and conceptualizing this kind of experiences.